Simple management of the neck platysma bands: a technique - Pedro, Clarós; Aleksandra, Sobolewska; Andrés, Clarós (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The aging effect of the neck is characterized by loss of elasticity and contractility of the skin. This aging is manifested clinically by the projection of the platysma bands, the redundancy of the skin, the accumulation of fat in the sub-mental, sub-mandibular regions, and the loss of the cervical-mental angle. Besides of face-lifting, there are other techniques for solving the aesthetic problems of platysma bands. This report aims to present our technique of the simple management of the platysma bands. We report our experience with the correction of platysma bands. The procedure is performed under local anaesthesia. The incision involves the skin and subcutaneous tissue; going from the lateral to the medial edge of the platysma band without cutting the muscle. The dissection of the muscle is continued to the deep side of the bands. This dissection is meticulous to preserve the superficial facial anastomotic plexus and the branch of the transverse cervical nerve afterward the muscle is cut. The technique mainly concerns individuals between the 4th and 6th decades. Women appear to be more concerned about the aesthetic appearance of their neck than men are. This technique is a simple surgical method, and in the majority of the cases, the results are satisfactory. It can be used alone or combined with face lifting. The technique of aesthetic treatment of platysma bands is a simple, effective surgical procedure and in most cases, the results are satisfactory.